Deterministic Irreversibility and The Matter Structure - Somsikov, Vyacheslav Michailovich (JOURNAL OF ADVANCES IN PHYSICS, 2019)
The role of existence of the deterministic irreversibility mechanism in development of evolution physics is studied. The short explanation of physical essence of this mechanism is offered. Based on this mechanism, is proved, that the base element of matter should be an open non-equilibrium dynamic system (ONDS). The principles of the emergence, existence and development of the ONDS hierarchical structure are considered. The questions about hierarchy of the matter and existence of stationary states ONDS are studied. The question, how external constraints determine of the evolution of ONDS, is analyzed. Equations that determine the development of ONDS are submitted.